Stare decisis in syariah - Ahmad, Muhamad Hassan; Mikail, Sa'id Adekunle; Ali Mohamed, Ashgar Ali; Ansari, Abdul Haseeb (CLJ Publication, 2020)
Due to this conflicting subject under the Syariah legal system in various countries as noted above, a question arises relating to the feasibility of the application of the doctrine of judicial precedent in Syariah Courts. Hence, this chapter discusses the feasibility of the application of the doctrine of judicial precedent in Islamic legal syste